O discurso do cotidiano nos fanzines punks brasileiros (1981-2010). - Fernandes., Alessandro Wilson Gonçalves Reinaldo (2013)
The punk movement in Brazil has transformed itself over the past three decades (1981-2010): joined new elements and, going beyond music, merged flags of political struggle and modified them. The fanzines (handmade independent publications) made by this movement also were ahead of these transformations, organizing the discursive meanings in punk countercultural quotidian. Investigating the discursive set that is present in these fanzines,our goal is analyze the transformations in this movement's quotidian, understanding its possibilities and its political limits of acting. Therefore, it is necessary to discuss the following elements: a) what is this medium, fanzines, its history and its relationship with the field of alternative communication and; b) those who produce this medium, the punk movement, understanding this social subject as an expression of social category of youth. It is noteworthy that the study starts from theoretical and methodological referential of marxist quotidian, with the qualitative method of Discourse Analysis.